ULUSLARARASI İNŞAAT SÖZLEŞMELERİNDE ESASA UYGULANACAK HUKUK BAKIMINDAN FIDIC SÖZLEŞME ŞARTLARININ VE MÖHUK m. 24/4'TE BELİRLENEN İSTİSNA KURALININ İNCELENMESİ - (:unkn) unknown (My University, 2016)
Uluslararası inşaat sözleşmeleri, teknik özelliklere sahip olan, yüksek meblağlı inşaat projelerinin gerçekleştirilmesi amacıyla yapılan ve sözleşme taraflarının hak ve borçları da dikkate alındığında karmaşık nitelikli sözleşmelerdir. Bu nedenle, tarafların hukuk seçimi yapmaları öngörülebilirlik ve belirlilik açısından tarafların lehinedir. Taraflar, ayrıca, Fidic standart sözleşme şartlarını incorporation teorisi kapsamında sözleşmenin parçası haline getirebilirler. Bununla birlikte, milli mahkemelerde yapılacak yargılamalarda bu durum hukuk seçimi teşkil etmeyecektir. Milletlerarası tahkim yargılamasında ise bu standart sözleşme şartları hukuk kuralları olarak uygulanabilecektir. Tarafların hukuk seçimi yapmaması durumunda, uluslararası inşaat sözleşmelerine uygulanacak hukuk objektif bağlama kuralına göre yüklenicinin işyerinin bulunduğu ülke hukuku olacaktır. Bununla birlikte, ifa yeri ülkesinin uluslararası inşaat projelerinde taşıdığı önem istisna kuralına dayanarak ifa yeri ülkesi hukukunun uygulanmasına neden olabilecektir. Bu makalede, öncelikle, inşaat sözleşmeleri maddi hukuk düzenlemesi bakımından ele alınmış, daha sonra ise uluslararası inşaat sözleşmelerine uygulanacak hukukun hukuk seçimi yolu ile veya objektif bağlama kuralı ya da istisna kuralının uygulanması yolu ile belirlenmesi incelenmiştir.

International construction contracts has some technical particularities and they are signed to realize construction projects with exorbitant sum of money. Moreover, when the rights and obligations of the contracting parties are considered, these contracts are complex in nature. Therefore, choosing an applicable law to the contract is advantegous to the parties in terms of predictability and certainty. In addition to this, contracting parties can incorporate the Fidic standard contract conditions to the construction contract between them. However, this will not be regarded as a choice of law in national courts. In international arbitration, these contract conditions can be applied as rules of law. If the parties do not make a choice of law, according to the objective rule, applicable law of the contract will be the law of the country, where the constructor has its' place of business. However, the significance of the country of place of performance with regard to the international construction projects can result in the application of the law of the country of place of performance which is characteristic to the contract, according to the more closely connection criteria. In this article, firstly, construction contracts are studied from the point of substantive law. Then, determination of applicable law to international construction contracts through choice of law or based on objective rule or the more closely connection criteria is studied.
Examination of the FIDIC Conditions of Contract and the Exception Rule in art. 24/4 of the Private International Law Code in respect to the Applicable Law to the Substance of International Construction Contracts
Keywords: Hukuk